Probabilistic Impact Assessment Of Electric Vehicle Charging On Malaysia Low-Voltage Distribution Networks - Tie, Chin Ho; Gan, Chin Kim; Ibrahim, Khairul Anwar (Indian Society Of Education And Environment & Informatics Publishing Limited, 2015)
-